2021
DOI: 10.1186/s12933-021-01369-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of canagliflozin on N-terminal pro-brain natriuretic peptide in patients with type 2 diabetes and chronic heart failure according to baseline use of glucose-lowering agents

Abstract: Background Sodium–glucose cotransporter 2 (SGLT2) inhibitors reduce the risk of a deterioration in heart failure (HF) and mortality in patients with a broad range of cardiovascular risks. Recent guidelines recommend considering the use of SGLT2 inhibitors in patients with type 2 diabetes (T2D) and HF, irrespective of their glycemic control status and background use of other glucose-lowering agents including metformin. However, only a small number of studies have investigated whether the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…Also, these parameters were significantly correlated with each other. Similarly, lower NT-pro-BNP levels were found after SGLT-2 inhibitor treatment in other studies involving patients with HF 15 , 16 . In some studies, improvement in exercise capacity, quality of life, and NYHA class were observed in patients with symptomatic HF after SGLT-2 inhibitor treatment 16 , 17 .…”
Section: Discussionsupporting
confidence: 67%
“…Also, these parameters were significantly correlated with each other. Similarly, lower NT-pro-BNP levels were found after SGLT-2 inhibitor treatment in other studies involving patients with HF 15 , 16 . In some studies, improvement in exercise capacity, quality of life, and NYHA class were observed in patients with symptomatic HF after SGLT-2 inhibitor treatment 16 , 17 .…”
Section: Discussionsupporting
confidence: 67%
“…The median NT-proBNP levels in each treatment group are shown in Table 1 . Detailed information on background medications for T2D and chronic HF have been previously shown elsewhere [ 9 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…The median NT-proBNP levels in each treatment group are shown in Table 1. Detailed information on background medications for T2D and chronic HF have been previously shown elsewhere [9,13]. Table 1 shows the baseline demographics and clinical characteristics for the full analysis set, stratified by baseline BMI.…”
Section: Baseline Clinical Characteristicsmentioning
confidence: 99%
“…To investigate the influence of baseline serum insulin levels on treatment effects for those parameters at week 24, data were analyzed using linear regression models for NT-proBNP and linear mixed models for other parameters in subgroups according to baseline serum insulin level. The ratio (canagliflozin vs. glimepiride) of the proportional change from baseline to week 24 in NT-proBNP was estimated based on a natural logarithmic scale [ 28 ]. A p - value for the interaction between the study treatments and baseline serum insulin category on the NYHA class was calculated using an ordinal logistic regression model analysis.…”
Section: Methodsmentioning
confidence: 99%